2021
DOI: 10.1021/acs.macromol.1c00004
|View full text |Cite
|
Sign up to set email alerts
|

Dienes Polymerization: Where We Are and What Lies Ahead

Abstract: Recently, the research activity in the field of the stereospecific polymerization of conjugated dienes has focused on the use of catalysts based on organometallic complexes having a well-defined structure and containing ligands of various types (e.g., phosphines, bis-imines, and pyridylimines), since it has been observed that the nature of the ligand, as expected on the basis of the diene polymerization mechanism proposed several years ago by Porri, is able to exert a strong influence on the polymerization reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 260 publications
3
93
0
4
Order By: Relevance
“…Most of the work carried out concerned, in particular, cobalt-based catalysts and, to a lesser extent, chromium, vanadium, titanium, zirconium, and lanthanide (neodymium in particular) derivatives. 14 Recently, however, there has been a considerable rediscovery of iron-based systems, 15−46 which have proved to be extremely active, selective, in some cases with living characteristics, and capable of polymerizing different types of conjugated dienes (e.g., 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 3-methyl-1,3-pentadiene), affording stereoregular polymers having different structures depending on the monomer employed. 47−51 This last feature specifically allowed us to improve and confirm our knowledge on the conjugated diene polymerization mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the work carried out concerned, in particular, cobalt-based catalysts and, to a lesser extent, chromium, vanadium, titanium, zirconium, and lanthanide (neodymium in particular) derivatives. 14 Recently, however, there has been a considerable rediscovery of iron-based systems, 15−46 which have proved to be extremely active, selective, in some cases with living characteristics, and capable of polymerizing different types of conjugated dienes (e.g., 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 3-methyl-1,3-pentadiene), affording stereoregular polymers having different structures depending on the monomer employed. 47−51 This last feature specifically allowed us to improve and confirm our knowledge on the conjugated diene polymerization mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research activity in the field of stereospecific polymerization of 1,3-dienes has mainly focused on the study of catalytic systems based on transition metal and lanthanide complexes with various organic ligands having N, O, and P as donor atoms. The interest in these complexes having a well-defined structure is due to the fact that the ligand nature plays a fundamental role in determining the polymerization regio- and stereoselectivity, in controlling the polymer molecular weight and the molecular weight distribution, and in providing, in some cases, living features to the catalysts themselves, thus allowing for the preparation of block copolymers. Most of the work carried out concerned, in particular, cobalt-based catalysts and, to a lesser extent, chromium, vanadium, titanium, zirconium, and lanthanide (neodymium in particular) derivatives . Recently, however, there has been a considerable rediscovery of iron-based systems, which have proved to be extremely active, selective, in some cases with living characteristics, and capable of polymerizing different types of conjugated dienes (e.g., 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 3-methyl-1,3-pentadiene), affording stereoregular polymers having different structures depending on the monomer employed. This last feature specifically allowed us to improve and confirm our knowledge on the conjugated diene polymerization mechanism …”
Section: Introductionmentioning
confidence: 99%
“…Cobalt-based catalysts were intensively investigated for the stereoregular polymerization of 1,3 alkadienes, and therefore are a viable candidates for the terpene polymerization. [62] Gong et al reported the first example of Co(II) catalyst (39) (Figure 10) in the copolymerization of M with I, using 39/AlEt 2 Cl (30 °C, 1-2 h, toluene) in a living cis-1,4 fashion (86.7-92.4 mol %). After consumption of I, the sequential addition of M provided poly(I-b-M) with M n up to 95.3 kg mol À 1 and very narrow Ð (1.05-1.09).…”
Section: Cobaltmentioning
confidence: 99%
“…Over the past decades, chemical and engineering research on isoprene polymerization, in both academia and industry, has led to major advances in the fields of rubber technology and stereoselective polymerization. Today, isoprene polymerization represents a benchmark reaction for every novel diene polymerization initiator (Figure A). Aside from isoprene polymerization, and to a lesser extent myrcene polymerization, only scattered studies have focused on the homopolymerization of non-naturally occurring 2-substituted 1,3-dienes, a situation that can be ascribed to the limited synthetic availability of these building blocks until recently. Consequently, the field clearly bears enormous potential becauseaside from stereochemical considerationssubtle variations on the nature of the diene substituent are expected to strongly impact the macromolecular properties of the resulting polymer.…”
Section: Introductionmentioning
confidence: 99%